2009
DOI: 10.1007/s00401-008-0481-0
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer disease macrophages shuttle amyloid-beta from neurons to vessels, contributing to amyloid angiopathy

Abstract: Neuronal accumulation of oligomeric amyloid-β (Aβ) is considered the proximal cause of neuronal demise in Alzheimer disease (AD) patients. Blood-borne macrophages might reduce Aβ stress to neurons by immigration into the brain and phagocytosis of Aβ. We tested migration and export across a blood-brain barrier model, and phagocytosis and clearance of Aβ by AD and normal subjects’ macrophages. Both AD and normal macrophages were inhibited in Aβ export across the blood-brain barrier due to adherence of Aβ-engorge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
106
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(111 citation statements)
references
References 51 publications
2
106
0
3
Order By: Relevance
“…Our results indicate that microglia from aged (15 month old) mice internalize 0.279ng/ml of Aβ42 (Fig 5A). In similar experiments recently performed by Zaghi et al, monocytes from aged humans (mean age:77years) are reported to internalize 0.256 ng/ml of Aβ42, a value within 8% of our findings in aged mouse microglia (Zaghi, et al, 2009). Because circulating monocytes are under certain conditions able to infiltrate the parenchyma, differentiate into microglia (Mildner, et al, 2007,Simard and Rivest, 2004) and modify amyloidosis (Simard, et al, 2006), the similarity of our measurements to human monocyte measurements indicates a strong possibility that our experiments model human physiology.…”
Section: Resultssupporting
confidence: 91%
“…Our results indicate that microglia from aged (15 month old) mice internalize 0.279ng/ml of Aβ42 (Fig 5A). In similar experiments recently performed by Zaghi et al, monocytes from aged humans (mean age:77years) are reported to internalize 0.256 ng/ml of Aβ42, a value within 8% of our findings in aged mouse microglia (Zaghi, et al, 2009). Because circulating monocytes are under certain conditions able to infiltrate the parenchyma, differentiate into microglia (Mildner, et al, 2007,Simard and Rivest, 2004) and modify amyloidosis (Simard, et al, 2006), the similarity of our measurements to human monocyte measurements indicates a strong possibility that our experiments model human physiology.…”
Section: Resultssupporting
confidence: 91%
“…Accumulations of Aβ in the periphery can similarly be phagocytosed by monocytes and neutrophils in the blood, and by macrophages in tissues 41 . Of note, in transgenic mice with AD, expression of Aβ scavenger receptors and Aβ-degrading enzymes in circulating mononuclear phagocytes decreases substantially as these mice age 42 , and the phagocytic functions of these cells are impaired in both mice and humans with AD [43][44][45] . Infusion of monocytes derived from peripheral human umbilical cord blood reduces the Aβ burden and improves cognitive deficits in a mouse model of AD 46 , implying that peripheral mononuclear phagocytes have an important role in Aβ clearance.…”
Section: Disorders Of Systemic Immunitymentioning
confidence: 99%
“…A significant decrease of this material was observed within 1 week, and it was below the detection limit at 1 month after inoculation. The uptake and degradation of A␤ aggregates by cells of the monocyte lineage is well documented (Majumdar et al, 2008;Zaghi et al, 2009;Lai and McLaurin, 2012;Michaud et al, 2013). We have shown recently that A␤ seeds are partly proteinase-K resistant (Langer et al, 2011), and insufficient clearance of A␤ seeds within cells has been shown to contribute to cell-to-cell spread of the seeds (Domert et al, 2014).…”
Section: Discussionmentioning
confidence: 99%